Edukasi Menstrual Hygiene sebagai Upaya Preventif Gangguan Kesehatan Reproduksi pada Remaja Putri - Nurjanah, Ramadhani Anggi Wahyu (Universitas Sebelas Maret, 2023)
Adolescence is a period that is vulnerable to reproductive health problems. One of the problems is about the cleanliness of the genital organs during menstruation. Information about genital hygiene during menstruation is very important for young women, including the knowledge of adolescents to prevent early infection of the reproductive organs. The right strategy to increase knowledge about menstrual hygiene is to provide health education. The purpose of this community service is as an effort to prevent reproductive health problems through increasing knowledge about menstrual hygiene in young women. Participants in this activity were given online education at zoom meetings through power point media and e-posters. The results of this educational activity for adolescents show that after being given education the knowledge of young women seems to increase, this can be seen from the majority of participants being able to answer the post test questions in the form of cases correctly. The conclusion from this community service is that education using power point media and e-posters can influence young women's knowledge about menstrual hygiene so as to increase efforts to prevent reproductive organ disorders.